FAKTOR RISIKO OPERASI BERULANG PASCA ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - Luh Putu Surya Sintia Dewi; Anak Agung Gede Eka Septian Utama (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background: ACL reconstruction (ACLR) is a surgical procedure to graft the ACL using tendon tissue to restore joint fixation and stabilization functions. Rehabilitation management is performed by physiotherapy in ACLR phase III patients to increase strength, balance, and functional motion control of patients with rehabilitation and exercise adaptation interventions. Case Description: On June 09, 2022, the patient was playing basketball, when the patient heard his leg